PENGARUH PAJAK, MULTINASIONALITAS, DAN TUNNELING INCENTIVE TERHADAP KEPUTUSAN TRANSFER PRICING - Rifqiyati (2021)
This study aims to determine the effect of taxes, multinationality, and tunneling incentive on the decision on transfer pricing in non-financial sector companies listed on the Indonesian Stock Exchange in 2017-2019. This research uses quantitative research methods with secondary data from financial and annual reports. This study has a sample of 53 non-financials sector companies. Testing the hypothesis is used multiple linear regression analysis with panel data on Stata 16.0. The data analysis technique used is the regression model selection test, classic assumption test, multiple regression analysis test and hypothesis testing consist of t-test, f-test, and regression model feasibility test. Based on the results of data analysis, it can be concluded that (1) taxes has a positive and significant effect on the decision on transfer pricing, (2) multinationality has a positive and significant effect on the decision on transfer pricing, (3) tunneling incentive has no effect on the decision on transfer pricing.